Agrarian Conflict and Legal Protection for Indigenous Peoples in North Sumatra - Ariston Bachtiar Limbong; Ica Karina (Inovasi Pratama Internasional. Ltd, 2026)
Agrarian conflicts involving indigenous communities in North Sumatra continue to escalate, threatening both tenure security and community well-being. This study quantitatively examines the relationship between the level of legal protection afforded to indigenous peoples and the intensity of agrarian conflict, along with its subsequent health consequences. A cross-sectional survey was conducted among 412 households across fifteen indigenous villages representing six ethnic groups. A Legal Protection Index was constructed based on land certification, customary forest recognition, access to legal aid, and perceived institutional effectiveness. Conflict intensity was measured through reported land disputes and violence, while health outcomes were assessed via self-reported stress, somatic symptoms, and conflict-related injuries. Descriptive analysis revealed that 68% of households had experienced at least one land dispute in the past five years, with corporate land grabbing being the dominant form. Multiple linear regression models demonstrated that a one-unit increase in the Legal Protection Index was significantly associated with a 0.47 reduction in conflict intensity (p<0.001) and a 0.39 decrease in poor health scores (p<0.001), after controlling for socio-demographic variables. Mediation analysis confirmed that legal protection indirectly protects health through dampening conflict. These findings underscore that deficient legal recognition of customary land rights exacerbates violent disputes and deteriorates indigenous health. Strengthening legal pluralism through formal recognition of adat territories and community-based paralegal services is an urgent public health and justice imperative